2014
DOI: 10.1002/fedr.201400023
|View full text |Cite
|
Sign up to set email alerts
|

Impact of waste water discharge on the plant communities and size structure of Wadi El‐Shees, Al‐Jabal Al‐Akhdar, Libya

Abstract: The present study assesses the impact of waste water discharge on the plant communities and size structure of the common woody species in Wadi El‐Shees, Al‐Jabal Al‐Akhdar, Libya. Thirty stands were selected along two adjacent tributaries (polluted and un‐polluted) in Wadi El‐Shees. Sixty‐five species belonging to 60 genera and 34 families were recorded, predominated with therophytes and mono‐regional taxa and only one endemic species (Arbutus pavarii). The application of TWINSPAN on the data set, led to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
3
2
1
Order By: Relevance
“…Application of TWINSPAN classification technique on the sampled stands in the present study resulted in 8 vegetation groups: 4 represented the polluted site, 2 for the non-polluted site and other 2 in both sites. The most dominant species were S. spinosum and J. phoenicea; this coincided with the study of Shaltout et al (2014), who recorded S. spinosum and J. phoenicea as dominant species in the polluted areas in this region. They also reported that the polluted areas were more diverse than the non-polluted ones, while the present study indicated that the vegetation groups of non-polluted sites were more diverse than that of the polluted ones, which coincided with the studies of Hegazy et al (2011) andAl-Sodany et al (2003) at Al-Gabal Al-Akhdr.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Application of TWINSPAN classification technique on the sampled stands in the present study resulted in 8 vegetation groups: 4 represented the polluted site, 2 for the non-polluted site and other 2 in both sites. The most dominant species were S. spinosum and J. phoenicea; this coincided with the study of Shaltout et al (2014), who recorded S. spinosum and J. phoenicea as dominant species in the polluted areas in this region. They also reported that the polluted areas were more diverse than the non-polluted ones, while the present study indicated that the vegetation groups of non-polluted sites were more diverse than that of the polluted ones, which coincided with the studies of Hegazy et al (2011) andAl-Sodany et al (2003) at Al-Gabal Al-Akhdr.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, concentrations of the heavy metals in the soil and waste water samples from the polluted sites were higher than those from the non-polluted sites; and all above the standard levels of Syrian Standard (0.01, 0.2, 0.1, 0.2 ug ml -1 for Cd, Cu, Cr and Ni, respectively). In the same region, this finding coincided with that of Shaltout et al (2014) who reported that the concentration of Cd and Cr were higher in the polluted areas than in the un-polluted ones.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These species are: Anabasis setifera, Arthrocnemum macrostachyum, Halopeplis perfoliate, Halocnemum strobilaceum, Haloxylon persicum, Haloxylon salicornicum, Salsola baryosma, Seidlitzia rosmarinus, Suaeda fruticosa and Suaeda vermiculata . It was clear from these figures that the polluted sited were less diverged than the unpolluted sited this differed from the findings of ( Shaltout et al, 2014 ) who claimed that the polluted sites were highly diverse in their vegetation cover as compared to unpolluted sites. However, our data were in line with those of ( Al-Sodany et al, 2003 , Hegazy et al, 2011 , Shaltout et al, 2015 ) who indicated that the vegetation cover in the unpolluted sites were highly diverged as compared to the vegetation cover of the polluted sites.…”
Section: Resultscontrasting
confidence: 81%
“…The application of TWINSPAN classification technique to the vegetation data produced seven groups and the application of DECORANA to the same data showed resemblances among some of these groups. Groups D, F and G were dominated by Juniperus phoenicea; this coincided with the study of Shaltout et al (2014).…”
Section: Discussionsupporting
confidence: 82%